Problem Solving dalam Perkuliahan Statistik Dasar - Mahendra, Rengga (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Statistik Dasar is one of the courses that must be taken by student Bimbingan Penyuluhan Islam departement, Faculty of Ushuluddin Adab dan Dakwah, IAIN Ponorogo. Statistik Dasar is a quite difficult courses for student because they have to understand material related to statistical test which are useful for analyzing quantitative type of thesis data. The aim of this research is to determine the effect of applying the Problem Solving learning model in Statistik Dasar lectures. This type of research is quasi-experimental using two classes of the Bimbingan Penyuluhan Islam departement, Faculty of Ushuluddin Adab dan Dakwah, IAIN Ponorogo. The research sample was taken using simple random sampling technique. Furthermore technical data analysis using t-test. The results of this research indicate that the application of the Problem Solving learning model can significantly improve student learning outcomes in Statistik Dasar lectures. This is because student who apply the Problem Solving learning model are accustomed to being active in constructing their knowledge and are more creative in solving problems related to statistical tests, thus making it easier for student to understand concepts and use statistical tests that are suitable for analyzing quantitative research data. Therefore, the Problem Solving learning model is very appropriate to apply in lectures, especially Statistik Dasar courses. Furthermore, the impact can increase the percentage of student Bimbingan Penyuluhan Islam departement who use quantitative research as their thesis assignment.